Choosing the right texts for the right level: analysing the readability of ‘English for Institutional Course’ (EFIC) textbook for the undergraduates / Untsa Rohmah Fadzillah and Kamisah Ariffin - Fadzillah, Untsa Rohmah; Ariffin, Kamisah (Universiti Teknologi MARA, Perlis, 2024)
Readability is an important aspect to be considered in the choice of educational materials as it has a significant influence on students' comprehension and learning outcomes. This study analysed the readability of the ‘English for Institutional Course’ (EFIC) textbook used for first-semester undergraduates in a university in Indonesia. As the book has not been assessed in terms of its readability, the study also aimed to determine the textbook's suitability for the university level students. The Flesch Reading Ease (FRE) formula was utilised as the framework for analysis. The data were procured from the reading texts of the EFIC textbook and the online tool of character calculator which incorporates the FRE formula was utilised to analyse the readability of the texts. The analysis revealed that five out of the eleven texts obtained the score of 80 and above, indicating that the textbook is easy and appropriate for primary and junior secondary education levels. This suggest that the textbooks may be too simple for tertiary education students. However, considering the FRE formula is based on and limited to the Western readability standards where English is the first language, its application to EFL contexts like Indonesia might not be entirely appropriate. Additionally, the textbook's range of readability levels may cater to varying student proficiency levels. Thus, the study concludes that while the EFIC textbook may seem easy from the readability score perspective, its suitability for the undergraduate level requires further consideration of contextual factors. The study also recommends for a localised readability assessment tool that is tailored to the context of local EFL learners be adapted, if not developed.